2013
DOI: 10.1016/j.jpor.2013.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of implant support on mandibular distal extension removable partial dentures: Relationship between denture supporting area and stress distribution

Abstract: This study indicated that implant placement at the distal edentulous ridge can prevent denture displacement of the distal extension bases, regardless of the supporting area of the denture base.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 19 publications
3
36
0
2
Order By: Relevance
“…In in vitro studies dealing with Kennedy class I or II situations, it has been demonstrated that positions more to the posterior reduce the pressure on the alveolar ridge and hence the periosteum more favorably in comparison to situations where implants are positioned more to the anterior . In situations with molar support the least amount of displacement of the mucosal tissues under load is seen . The present data clearly demonstrate an improvement in masticatory performance when implant support was provided 3 months earlier.…”
Section: Discussionsupporting
confidence: 57%
“…In in vitro studies dealing with Kennedy class I or II situations, it has been demonstrated that positions more to the posterior reduce the pressure on the alveolar ridge and hence the periosteum more favorably in comparison to situations where implants are positioned more to the anterior . In situations with molar support the least amount of displacement of the mucosal tissues under load is seen . The present data clearly demonstrate an improvement in masticatory performance when implant support was provided 3 months earlier.…”
Section: Discussionsupporting
confidence: 57%
“…El desplazamiento distal de la base se reduce, independientemente de la zona de apoyo de esta (Sato et al, 2013;de Freitas et al), además permite disminuir la extensión de la base protésica, otorgando al paciente una mayor comodidad y satisfacción, por la mejora en las características biomecánicas de las tradicionales PPR. Mitrani et al (2003) reportan escasa reabsorción ósea bajo la base protésica.…”
Section: Ventajas Y Desventajas De Ppri Como Alternativa De Tratamienunclassified
“…Moreover, the removable denture sinks slightly (approximately 100 µm) for about two weeks after delivery because the soft tissue under the denture base is deformed by masticatory loading [23][24][25][26][27] . Thus, temporary fixation materials should be used for the fixation of magnetic attachments at the time of denture delivery.…”
Section: Introductionmentioning
confidence: 99%